Long-Term Dynamic in Nutrients, Chlorophyll a, and Water Quality Parameters in a Coastal Lagoon During a Process of Eutrophication for Decades, a Sudden Break and a Relatively Rapid Recovery - Pérez-Ruzafa, Angel; Campillo, Sara; Fernández-Palacios, José María; García-Lacunza, Antonio; García-Oliva, Miriam; Ibañez, Helena; Navarro-Martínez, Pedro C.; Pérez-Marcos, María; Pérez-Ruzafa, Isabel M.; Quispe-Becerra, Jhoni Ismael; Sala-Mirete, Antonio; Sánchez, Olga; et al. (Frontiers in Marine Science, 2019)
Coastal lagoons are considered among the marine habitats with the highest biological productivity, and support a great variety of human activities and pressures that make them especially vulnerable to trophic imbalances. While dystrophic crises are common in many lagoons, others like the Mar Menor show homeostatic mechanisms, high resilience, and clear waters. This paper analyses the water column descriptors dynamic during the last 22 years in this coastal lagoon, in the context of a eutrophication process produced by an increase in nutrient inputs, mainly derived from agriculture. Despite water column nitrate concentration increased by one order of magnitude, the lagoon maintained homeostatic regulation for two decades, keeping the water transparency and relatively low levels of nutrients and chlorophyll a (Prebreak phase), followed by a sudden change of state in 2016 with an abrupt increase in average nutrients and chlorophyll a concentration and loss of water transparency (Break phase), and a relatively rapid recovery after the reduction of nutrient discharges (Recovery phase). The activation of the regulation mechanisms seems to manifest through an ammonium production in the water column, as a consequence of the activity in the trophic web. The low correlation between chlorophyll a and nutrients concentration, mainly at small spatio-temporal scales, is in disagreement with eutrophication traditional models, and suggests a rapid response of primary producers to nutrient inputs and a zooplankton control in the short-term, which in turn is controlled by the rest of the trophic web components. Homeostatic properties that in the Mar Menor lagoon have provided resistance to eutrophication are based on several mechanisms: channeling its production toward the benthic system (maintaining high biomasses of primary producers, filter feeders, and detritivores), a top-down control of the pelagic trophic web exerted by ichthyoplankton and jellyfish, and exporting surplus production outside the system. Resilience of the system would be based on the high turnover in the species composition related to the restricted connectivity to the sea, the spatio-temporal variability of the environmental conditions, and the multiplicity of spatial–temporal scales involved in lagoon processes. TRIX index was sensitive to the trophic and water quality changes. However, in our study, its current score does not allow to anticipate or alert the eutrophication risk and the trophic breakpoint of the system.